The determination of the embedment strength of Malaysian hardwood - Jumaat, Mohd Zamin; Bakar, Aishah Abu; Razali, Fadini Mohamad; Rahim, Ahmad Hazim Abdul; Othman, Johari (2006)
Research on determining the embedment strength of Malaysia timber species is currently being conducted. Prior to this, there is no data on the embedment strength of Malaysian timber available as there are no study been conducted locally which emphasize in this area. The experimental works on determining this fundamental parameter of a connection are being carried out on selected species of local hardwood timber. The species selected represents various joints groups. Data and results were analysed and using the embedment strength values approaches which are similar to those adopted in Europe, the basic load of timber joints to be used in the limit state design method will be forwarded for consideration to be incorporated in the Malaysian code of practice.